Roles involved in school violence: links with the problematic use of social networking sites, self-esteem, and loneliness in adolescents. - David Moreno-Ruiz; David Montero Montero; Ana Romero-Abrio; Gonzalo Musitu-Ochoa (Revista Española de Investigación Criminológica)
The objective was to analyse the relationships between multidimensional self-esteem (academic, social, emotional, family, and physical), loneliness, the problematic use of social networking sites (PUSNS) and the different roles involved in school violence - non-involved, aggressors, victims and victim-aggressors-, depending on sex. Participants included 1,930 adolescents (50.2% girls) aged 12 to 18 years, schooled in the province of Seville (Spain). A MANOVA (4x2) was performed. Significant relationships were observed between the different school violence roles, loneliness, multidimensional self-esteem, and PUSNS. Specifically, depending on the dependent variables analysed, victims-aggressors presented a more negative profile than the rest of the roles observed, and the non-involved showed the best adjustment. It is also remarkable that the groups with the lowest scores in PUSNS are the two groups of non-involved individuals, both boys and girls, and the group of male victims. To finish, we describe the practical implications of the study.